Raul Pompéia, leitor de Baudelaire: da teoria das correspondências às canções sem metro - Sandanello, Franco Baptista (Opiniães, 2011)
Although a part of the prose poem’s formal traditionas established by the Little poems in prose by CharlesBaudelaire, the Canções sem metro by Raul Pompéia,first national attempt of exercise in the genre, haveon its first section of poems a quatrain of the sonnet“Correspondances” for epigraph, a unity of the poemand sonnet book Flowers of evil. We intend to discussin this article which are the textual and which are thecontextual reasons for this likely “diversion of influences”in Pompéia’s text, and if they are or not open tothese opposite formal options nevertheless present inthe works of Baudelaire. To do so, we analyse the firstsection of Canções sem metro, the already mentioned“Correspondances” and one of the Little poems in prose.